2020
DOI: 10.1002/app.49766
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight polyethylene‐hollow glass microspheres composites for rotational molding technology

Abstract: Innovative composites based on polyethylene (PE) filled with hollow glass microspheres (HGMs) were formulated and successfully prepared as suitable plastic materials for rotational molding technology. The HGMs here used allow to attain lightweight materials with a reduced resin content and appealing aesthetical qualities. To enhance filler dispersion and phase adhesion, thus improving the ultimate properties of the composite materials, two compatibilization strategies were adopted: namely, surface modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…These same authors later used glass fiber dust, a residue from wires insulation, into an LDPE matrix at 20% loading, blending both materials in a high-speed mixer to reduce the thermal degradation from the molten compounding, obtaining moderate increases in mechanical properties, even in impact strength [ 19 ]. Glass particles have also been proposed as reinforcement of PE in up to 20% [ 30 ]; this research highlights the importance of using a coupling agent, such as maleic anhydride grafted polyethylene, to improve interfacial bonding and ultimately the composite’s performance. The addition of such a compound results in higher increases in elastic modulus and avoids the decrease in tensile strength observed for composites without that compound.…”
Section: Analysis Of the Retrieved Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These same authors later used glass fiber dust, a residue from wires insulation, into an LDPE matrix at 20% loading, blending both materials in a high-speed mixer to reduce the thermal degradation from the molten compounding, obtaining moderate increases in mechanical properties, even in impact strength [ 19 ]. Glass particles have also been proposed as reinforcement of PE in up to 20% [ 30 ]; this research highlights the importance of using a coupling agent, such as maleic anhydride grafted polyethylene, to improve interfacial bonding and ultimately the composite’s performance. The addition of such a compound results in higher increases in elastic modulus and avoids the decrease in tensile strength observed for composites without that compound.…”
Section: Analysis Of the Retrieved Workmentioning
confidence: 99%
“…They have found that the treatment of the glass particles is needed to increase the tensile modulus of composites and to avoid a reduction in tensile strength. The surface treatment proposed by these authors consisted of a first step of hydroxylation with NaOH, followed by a later silanization, as also presented by Stagnaro for PE-based composites [ 30 ].…”
Section: Analysis Of the Retrieved Workmentioning
confidence: 99%
“…The uniaxial rotational molding for this material can be successfully conducted [ 8 ]. Since the preparation of composite materials in rotational molding technology is receiving increased interest [ 1 , 9 , 10 ], the works discussing possibilities of preparing those composites in uniaxial rotational molding also increase. One of these kinds of works discusses the production of PE composites filled with hollow glass microspheres (HGM) [ 10 ], and another paper concerns the same filler but in a different polymeric matrix, mainly poly(caprolactone) (PCL) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the preparation of composite materials in rotational molding technology is receiving increased interest [ 1 , 9 , 10 ], the works discussing possibilities of preparing those composites in uniaxial rotational molding also increase. One of these kinds of works discusses the production of PE composites filled with hollow glass microspheres (HGM) [ 10 ], and another paper concerns the same filler but in a different polymeric matrix, mainly poly(caprolactone) (PCL) [ 11 ]. In both these studies, fillers were submitted to a surface treatment, which was a two-step process; firstly, HGM particles were hydroxylated and then silanized to increase the adhesion between the polymer matrix and filler.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, crystallization, occurring during the cooling step, is of great importance for the morphology and the resulting properties of the final product. Several studies were focused on polyethylene-based materials in order to investigate crystallization during the RM process [ 4 , 5 , 6 , 7 ] and the final properties of the rotomolded composites [ 8 , 9 , 10 , 11 , 12 , 13 ]. However, the recent growing interest for RM aimed to investigate the crystallization behavior of other polymers such as polypropylene [ 14 , 15 ], polyamide [ 16 ], and polylactide [ 17 , 18 ] for application in this technology process.…”
Section: Introductionmentioning
confidence: 99%